Tajikistan : Country Environmental Analysis - World Bank (Washington, DC, 2012)
Tajikistan is a small mountainous land-locked Central Asian country with an economy that heavily depends, as a legacy of the soviet economy, on exports of cotton, aluminum and hydroelectricity that are three rather environmentally sensitive sectors, as well as on remittances from migrants living abroad. Environmental degradation and unsustainable use of natural resources are constraints to sustainable economic growth and poverty reduction. With more than half of its territory situated above 3,000 meters, the country is particularly vulnerable to natural disasters. The environmental challenges in the country, according to the recent National Environmental Action Plan (NEAP) is: (i) land degradation, including deforestation, degradation of pasturelands, arable and irrigated lands; (ii) lack of improved drinking water and water quality deterioration; (iii) waste pollution from agriculture and industry; (iv) deficiencies in sewerage system infrastructure and management; (v) uncollected and untreated solid waste; (vi) environmental hazards and natural disasters caused by floods and drought; (vii) energy supply; and (viii) lack of environmental education.